Benefits of management systems integration: a literature review. (1st May 2015) - Bernardo, Merce; Simon, Alexandra; Tarí, Juan José; Molina-Azorín, José F.
Abstract: The purpose of this paper is to identify the benefits of integrated management systems by comparing them with the benefits obtained through the individual implementation of ISO 9001 and ISO 14001 standards. The methodology used is a literature review based on an electronic search in the Web of Science, ScienceDirect, Scopus and Emerald databases. Findings show that although some benefits are common regardless the system management type, the benefits obtained with integration are greater than considering management systems separately because of the wider scope considered in integration. This is one of the first papers, to the best of our knowledge, to compare benefits from the two management systems standards when implemented separately and when integrated. In addition, some ideas are proposed for consideration in future research on the internalization of management systems and selection effect. Highlights: Benefits of MSs are greater than managing MSs separately. Internal and external benefits of integration are detected. Integration benefits impact in the entire organization.